PORTFOLIO PERFORMANCE ANALYSIS OF THE SHARPE METHOD ON THE INDONESIAN SHARIA STOCK INDEX - Tania, Atika Lusi; Yudistira, Era; Apridasari, Esty (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
Diversifying the stock portfolio can reduce the high risk of stock investment. The Sharpe method calculates the optimal portfolio by optimizing the ratio angle of excess returns and standard deviation risk of the portfolio. The Sharpe method is a portfolio method that compares returns and risks, the higher the Sharpe value, the better the performance of the portfolio. This ratio is used because it is popularly used as a mutual fund calculation compared to other methods such as the Simple Method. The purpose of this study is to find out how the stock portfolio is with the Sharpe method and how the combination of stocks is from that method. Based on the calculations and discussions that have been done, it can be concluded that the Sharpe method of portfolio analysis obtained only two assets that have the most significant angle, which means they have the best performance. Previously, 30 shares of IDX Syariah Growth were used, then 10 shares with the smallest and positive coefficient of variance were obtained. The ten shares are ADRO, AGII, ANTM, BRIS, BTPS, HRUM, INCO, ISAT, ITMG, and SIDO. After calculating by looking for the most significant angle, two combinations of stocks with the best performance were obtained, namely ADRO and ISAT. The best stock combinations using the Sharpe method acquired shares with the ADRO code of 70% and ISAT of 30%. It is expected that further research will also calculate stock performance in ASEAN countries